(untitled) (Communications in Mathematical Research, 2021)
This paper deals with the existence of positive solutions to a singular fourth order coupled system with integral boundary conditions. Since the nonlinear terms f, g may change sign or be singular at t = 0 or t = 1, the authors make a priori estimates to overcome some difficulties and apply Guo-Krasnoselskii fixed point theorem to prove the existence of solutions of the system under suitable assumptions. Finally, some examples to illustrate the main results are given.